Beauty Pays, But Not Under All Circumstances: Evidence on Gendered Hiring Discrimination from a Novel Experimental Treatment Using Deepfakes - Kühn, Juliane; Wolbring, Tobias (Research in Social Stratification and Mobility, 2024)

Is informedness the key? An empirical analysis of VET dropouts in Germany - Herrmann, Lisa; Kühn, Juliane (Empirical Research in Vocational Education and Training, 2024)
In 2022, one in four vocational education and training (VET) contracts resulted in premature termination—a potential sign of inefficiency in the training of urgently needed skilled professionals. This study focuses on the level of perceived informedness of trainees and its potential influence on dropout. This includes trainees’ perceived level of information about the characteristics and requirements of an occupation, which may result from various sources of information in the form of social contacts. We draw on theories from the field of career choice and job search to argue that a better level of informedness can reduce uncertainty and enable individuals to make better-informed decisions about their careers. With better informedness, there is a higher probability of finding a suitable match between a trainee and their chosen occupation, ultimately increasing their likelihood of job persistence. This should also lead to a lower probability of dropout among VETs. Using data from the National Educational Panel Study, starting cohort 4, we employed event history analysis. We show that good perceived informedness on the requirements of one’s vocational training and the perception of good school-based vocational preparation reduce the probability of dropping out. In contrast, good informedness about alternative training programs increases dropout risk. We also see that the distinction between closer or more distant groups of people from the social network (strong or weak ties) who provide information about training is not decisive.
CRIS-Team Scopus Importer:2024-10-25
Keywords: Dropout; Informedness; Level of information; NEPS; Vocational education and training (VET)

Using deepfakes for experiments in the social sciences–A pilot study - Eberl, Andreas; Kühn, Juliane; Wolbring, Tobias (Frontiers in Sociology, 2022)
Keywords: Diskriminierung